Transformation of a Sole Proprietorship Into a Limited Liability Company - Jaworska, Agnieszka (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The introduction of the provisions of the Polish Order (“Polski Ład”) raised numerous doubts among persons conducting business activity. The regulations resulted in many entrepreneurs deciding to cease their business activity or to transform their so-far sole proprietorship into other forms of business in order to avoid unfavourable taxation. Among those who decided to transform their business, the decision to transform into a limited liability company prevailed. In this article I would like to discuss the reasons for and procedure of transforming a sole trader into a limited liability company.